Diseño de un Plan Modelo de Mantenimiento para Edificios del ICE - Camacho-Salazar, Pablo (Instituto Tecnológico de Costa Rica, 2009)
This document contains the procedures used to design a Model Maintenance Plan for buildings of the Instituto Costarricense de Electricidad (ICE). The goal of this project is to document the tools used to plan the building maintenance. It is expected that the proposed design could be emulated and applied to other buildings. The functionability of the system elaborated was based on the “Torre Z” building, which consists of 4 409 m2 of construction. It is located in San Pedro of Montes Oca, San Jose and houses administrative offices of the Division of Services and Security Division of the ICE, in particular. The maintenance plan was focused in the inclusion of preventive maintenance to a system that works totally corrective and in creating a tool that allows the creation of historical maintenance records. By means of maintenance cycles guides, periodic inspections, programmed interventions and a system of database generation it is obtained a method to generate maintenance historical records (statistics). From these records it is possible to know the indexes of goods and services used to attend the needs of a building.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2009.
Keywords: Mantenimiento preventivo; Formulario de intervención; Formulario de inspección; Intervención programada; Mantenimiento correctivo